2005
DOI: 10.21273/hortsci.40.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Postbloom Humic- and Fulvic-based Zinc Sprays Can Improve Apple Zinc Nutrition

Abstract: Zinc supplied as a fulvic-based Zn compound was absorbed and retranslocated to unsprayed new growth as effectively as zinc sulphate in apple seedlings of low Zn status grown hydroponically in the greenhouse. Similarly, fulvic- and humic-based compounds were as effective as zinc sulphate at improving short-term growth and Zn uptake into new tissues in Zn-deficient apple seedlings, with the best growth occurring at spray concentrations of Zn at 500 mg·L-1. Under field conditions, Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…However, studies about the effects on fruit quality of different forms of foliar Zn applied at different stages of apple tree growth are very few. foliar spray of fulvic-and humic-based Zn compounds was equally or more effective than ZnSO 4 at being absorbed by vegetative apple seedling tissue (Neilsen et al, 2005), but whether the sugar alcohol zinc is effective has not been clear. Recently, sugar compounds containing Zn have been advocated for use with little information to support their use.…”
mentioning
confidence: 99%
“…However, studies about the effects on fruit quality of different forms of foliar Zn applied at different stages of apple tree growth are very few. foliar spray of fulvic-and humic-based Zn compounds was equally or more effective than ZnSO 4 at being absorbed by vegetative apple seedling tissue (Neilsen et al, 2005), but whether the sugar alcohol zinc is effective has not been clear. Recently, sugar compounds containing Zn have been advocated for use with little information to support their use.…”
mentioning
confidence: 99%
“…The important role of zinc, which functions as a cofactor in the structure and function of many enzymes (Jeffery et al, 1984;Hacisalihoglu et al, 2003;Andreini and Bertini, 2012), in various processes such as photosynthesis, carbohydrate metabolism and regulation of phytohormones (Hacisalihoglu et al, 2001;Krämer and Clemens, 2006;Alloway, 2008;Broadley et al, 2007;Gupta et al, 2011) can justify the influence of zinc on fruit quality characteristics in the study. As a matter of fact, Rodríguez et al (2005); Neilsen et al (2005); Khayyat et al (2007); Zhang et al (2013) have reported that zinc application can significantly improve fruit yield and quality in date palm, oranges and apples.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc deficiency causes decrease in leaves, shoots and photosynthesis rate and hence, it affects yield and quality on fruit trees (Wang and Jin, 2005;Yan et al, 2010). Foliar zinc treatment in date palm, oranges and apples can significantly increase the zinc concentration, fruit yield and quality (Rodríguez et al, 2005;Neilsen et al, 2005;Khayyat et al, 2007;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Using commercial products containing humic acid in pear production are very rarely reported in the literature, but some investigations have been conducted with these products in different fruits like orange and grapefruit (Alva andObreza, 1998), lemon (Sànchez-Sànchez et al, 2002), apple (Neilsen et al,. 2005) and date palm (Elboray et al, 2006).…”
Section: Introductionmentioning
confidence: 99%